Aggregation of excessive sedentary behaviors in schools - Rodrigo Mercês Reis Fonseca; Bruna Maria Palotino Ferreira; Cristiane dos Santos Silva; Thiago Amaral Martins; Hector Luiz Rodrigues Munaro (Journal of Physical Education (Maringá), 2025)
Objective: To estimate the prevalence and identify factors associated with the aggregation of four excessive sedentary behaviors (screen time watching television during weekdays and weekends, and screen time using computers/video games during weekdays and weekends) among public school students in Jequié, Bahia, Brazil. Methods: A cross-sectional study was conducted with high school students from the state school system in a city in Bahia, Brazil. The sedentary behaviors evaluated included screen time watching television and using computers or video games during weekdays and weekends. Sociodemographic and lifestyle variables were analyzed as predictors to identify factors associated with the aggregation of these behaviors (outcome). Associations were estimated using the Prevalence Ratio (PR) with a 95% confidence interval (CI). Results: The sample comprised 972 students, with a higher proportion of females (53.4%; n = 519). The highest prevalence of excessive sedentary behaviors was observed for screen time spent watching television and using computers/video games during weekends (24.6% and 25.1%, respectively). Female students were less likely to exhibit the aggregation of the four sedentary behaviors. However, students who were unemployed, insufficiently active, or did not consume adequate amounts of vegetables were more likely to exhibit the aggregation of these behaviors. Conclusions: A high level of aggregation of excessive sedentary behaviors was observed among the students. Sociodemographic and lifestyle factors, such as physical inactivity and inadequate dietary habits, were significant contributors to this outcome.